TREASURY STOCK: A SOURCE OF PROFIT OR LOSS? - Rankin, Calvin H. (The Accounting Review, 1940)
Accountants have often marveled at the misunderstanding of generally accepted accounting procedure and concepts, which the courts have in the past exhibited. Many decisions not only show misunderstanding but also indicate a failure on the part of the courts to attempt to ascertain the meaning of accounting terminology, which their decisions employ. It is unfortunate therefore to find a court in a recent tax decision turning for guidance to "correct accounting" as set forth in theory and practice only to find lack of agreement on the part of accountants as to theory and even greater disparity between theory and practice. It is only fair to state that the court found a similar lack of agreement on the question in the court decisions it examined. The "sale" of treasury shares can never result in "gain or loss." The question of "gain or loss" arises solely at the time of "purchase," not at the time of "sale." The account "treasury shares," carried on the books when stated capital has not been reduced as provided by law, represents an unallocated reduction and adjustment of shareholders' equities. If the treasury shares are later disposed of, the entire amount received from the new shareholder, should be recorded as any issue of stock, the par or stated value being credited to "Capital Stock" and the difference, if any being adjusted through surplus.